Rorty the reformer? (2008)
Rorty should be read as a reformer, rather than a revolutionary transformer. While the reformer aims to improve what is already good, the revolutionary transformer seeks to dispense with the merely good in a quest for the absolutely best. For Rorty this choice was a bad choice. In order to make the case that Rorty was a reformer, we explicate Rorty’s views on truth. These views argue that we can obtain consensus about what is worth preserving and improving without reference to either rightness, truth, or objectivity. For after all, there is no way for philosophers to get outside the circle of language within which we debate about what we take to be authoritative and aceptable.